Cloning and expression of a porcine zona pellucida gene: an approach to immunocontraception - Fontenot, Gregory Kenneth, author; Bowen, R. A., advisor; Carlson, Jonathan, committee member; Niswender, Gordon, committee member (Colorado State University. Libraries, 1991)
Immunization with native porcine zona pellucida (ZP) proteins has been shown to induce infertility in females of several species and is thus a potentially valuable method of contraception. However, more extensive testing and commercialization of such a vaccine has been hampered by the limited availability of ZP proteins from natural sources. Availability of recombinant ZP proteins should simplify production of a practical ZP vaccine. The objective of this research was to clone a porcine ZP gene and use it to develop a recombinant ZP vaccine for use in pet animals. Polyadenylated RNA isolated from swine ovary was used to generate a cDNA library in the bacteriophage lambda gt11. This library was screened immunologically for ZP sequences using a polyclonal antiserum raised against solubilized porcine ZP. One immunoreactive clone, PZP, contained an insert of approximately 2.6 kb and was characterized further. The three Eco RI fragments constituting PZP were isolated and subcloned into a plasmid vector. The amino acid sequence deduced from the nucleotide sequence of PZP is considered to represent 305 residues from the carboxyterminal end of the ZP protein. A putative N-glycosylation site is present at residue 288 of this polypeptide. Comparison of the deduced amino acid sequence of PZP with deduced protein sequences from all of the other ZP proteins published to date failed to reveal significant homology. To confirm that PZP represented a ZP mRNA, a 418 bp fragment of the cDNA was expressed as a fusion protein in E. coli and used to hyperimmunize a rabbit. Antibodies to the PZP fusion protein bound to ZP surrounding porcine oocytes, stained ZP in sections of porcine ovary and immunoprecipitated a porcine ZP protein that was tentatively identified as ZP2. The PZP fusion protein was preliminarily evaluated as a vaccine in rabbits. Two groups of four adult rabbits were immunized three or four times with PZP2 fusion protein emulsified in either one of two adjuvants. Reproductive function was evaluated eight and sixteen weeks after initial immunization. In comparison to control rabbits, no effect of vaccination on reproductive function was observed.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Zona pellucida; Molecular cloning; Contraception, Immunological